District councils- Between community and administration: The case of Poznan - Matczak, Piotr (The Greek Review of Social Research, 2016)
Communities in cities were transformed significantly in the second half of the twentieth century. Weaker social ties and growing individualism have been combined with the growing role of formal institutional structures. Local governments became increasingly dominated by central structures. Decentralisation emerged as an attempt to reform this tendency. This article presents and analyses district councils in Poznan in respect of their success in promoting public involvement, accountability, and efficiency of public services delivery. It is argued that their impact on accountability, public control of authority, public involvement, and public activity is not significant. Instead, growing distrust of district councillors towards the city can be observed. Moreover, despite certain minor differences in administration costs, the structure of districts’ expenses is relatively homogeneous which may lead to the conclusion that district councils do not help to adjust the services to the varied inhabitants’ preferences.